The Representation of Social Media in English Textbook: A Hallidayan Perspective - Seli, Fenny Yutika; Manar, Marsandi; Ciphani, Chairunnisa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This Hallidayan transitivity study explores how social media is represented in the reading texts of a nationally issued English textbook for Indonesian year-twelve students. In particular, this study aims to reveal the transitivity system patterns constructed in the reading materials about social media. This study adopted qualitative perspective as the approach and content/text analysis as the method. The data were reading materials of three chapters selected purposely from an English textbook. The reading texts then were analysed into Hallidayan six types of process, namely material, mental, behavioural, verbal, existential, and relational clauses.  After that, each process type was further analysed. The findings firstly reveal that material (55%), mental (30%), and relational clauses (12%) appear in sequence as the dominant process types. Other processes were also found in the data but their occurrences are limited, namely 1% for each of behavioural, verbal, and existential clauses. Secondly, the findings expose that each process type is patterned distinctively in representing different issues about social media. It is expected that the findings of this study contribute to how to represent events in English textbooks functionally so that the educational goal set by book can be obtained. Despite its findings, this study relies only on a single book as the data source. Further studies can make use of more data sets.